2019
DOI: 10.1021/acs.est.9b01345
|View full text |Cite
|
Sign up to set email alerts
|

Biochar-Mediated Anaerobic Oxidation of Methane

Abstract: Biochar was recently identified as an effective soil amendment for CH4 capture. Corresponding mechanisms are currently recognized to be from physical properties of biochar, providing a favorable growth environment for aerobic methanotrophs which perform aerobic methane (CH4) oxidation. However, our study shows that the chemical reactivity of biochar can also stimulate anaerobic oxidation of CH4 (AOM) by anaerobic methanotrophic archaea (ANME) of ANME-2d, which proposes another plausible mechanism for CH4 mitig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(63 citation statements)
references
References 41 publications
1
58
0
Order By: Relevance
“…Coulombic efficiency estimation showed that only 54.3% of electron recovery can be obtained against the assumption that the current output in this period was solely driven by AOM (Additional file 1: Table S1), which suggests that there was some other more oxidized carbonaceous substances contributed to the current output. This could be ascribed to the oxidation of intracellular storage substances present in methanotrophic biomass providing additional reducing equivalents, as previously discussed [30,31]. Afterwards, the current in the BEMR stabilized at around 149 mA m -2 when the HFMs was pressurized at 0.8 bar.…”
Section: Colonization Of Methanotrophic Biofilm On Hfmsmentioning
confidence: 52%
See 1 more Smart Citation
“…Coulombic efficiency estimation showed that only 54.3% of electron recovery can be obtained against the assumption that the current output in this period was solely driven by AOM (Additional file 1: Table S1), which suggests that there was some other more oxidized carbonaceous substances contributed to the current output. This could be ascribed to the oxidation of intracellular storage substances present in methanotrophic biomass providing additional reducing equivalents, as previously discussed [30,31]. Afterwards, the current in the BEMR stabilized at around 149 mA m -2 when the HFMs was pressurized at 0.8 bar.…”
Section: Colonization Of Methanotrophic Biofilm On Hfmsmentioning
confidence: 52%
“…Methanoperedens was the only candidate being responsible for CH 4 activation. Interestingly, organisms belonging to the genus Geobacter were also observed in the community enriched in BEMR, reaching a relative abundance of 2.4%, which could be stimulated by readily available intermediates (such as acetate) released by intracellular storage substances of methanotrophic biomass [30,31]. Regarding the Control-BES, the microbial community was also consistent with the inoculum when nitrate was fed in the first 147 days.…”
Section: Microbial Community Dynamicsmentioning
confidence: 89%
“…Materials on which biofilms attach may additionally affect microbial niches. Functional groups on the surface of materials can change the redox activities, benefiting some bacteria suitable for the specialized redox environment as well as affecting their metabolisms 36 . For example, bacteria with the DIET ability may need to initially produce conductive pili and other biological electrical connections, which make them grow slower.…”
Section: Enhancing Microbial Cooperation Within the Microbial Niche Nmentioning
confidence: 99%
“…Examples for in-situ mitigation are thus the collection and technical oxidation of landfill gas but the oxidation by methanotrophs in biotic covers of the landfill [109]. Methane emissions from soils can be reduced by supporting aeration of the soil and by creating a favorable growth environment for methanotrophs, for example, by adding biochar, but also other materials such as sand, slag, sludge, compost or wood pellets [151].…”
Section: In-situ Mitigationmentioning
confidence: 99%